Settings-free traveling wave based earth fault location using Unsynchronized two-terminal data - Lopes, Felipe Vigolvino (2015)
This Letter presents a two-terminal traveling wave (TW) based earth fault location algorithm. It works using unsynchronized data and does not require information about the line parameters. Evaluated signals are decoupled into aerial and ground modes and, then, only the incident TWs of each mode are detected at the line ends. Earth fault case studies are carried out to attest the proposed algorithm feasibility, comparing its performance with those of one- and two-terminal approaches reported in the literature. Obtained results reveal the proposed algorithm is straightforward and quite reliable.